Case Report: Atypical acute compartment syndrome of the forearm in a child following minor trauma with consecutive osteomyelitis - Everaert, J.; Delafontaine, A.; Juanos Cabanas, J.; Leclercq, G.; Jennart, H.; Baillon, B. (Frontiers in Surgery, 2024)
Introduction Forearm compartment syndrome (CS) in children is above all a clinical diagnosis whose main cause is traumatic. However, rarer causes such as infection can alter its clinical presentation. Clinical case An 8-year-old boy has been seen in the emergency department complaining of severe forearm pain under a splint in a mild traumatic context. The previous radiological imaging examination three days before had not revealed any fractures. On admission, he presented with major signs of skin inflammation, loss of mobility, paresthesia and a significant biological inflammatory syndrome. The acute CS diagnosis has been made and was treated, but its atypical presentation raised a series of etiological hypotheses, in particular infectious, even if it remains rare. Complementary imaging examinations confirmed the presence of osteomyelitis of the distal radius as well as an occult Salter-Harris II fracture. Discussion Beyond the classic “five P's of CS” -pain, paresthesia, paralysis, pallor and pulselessness-, CS's clinical presentations are multiple, especially in pediatric patients. In children, severe pain and increasing analgesic requirement must be indicators of a CS. We hypothesize that this patient sustained a nondisplaced Salter-Harris II fracture with a hematoma colonized by hematogenous osteomyelitis explaining its initial clinical presentation. Conclusion Hematogenous osteomyelitis complicated by CS is rare and may be accompanied by a traumatic history. It's atypical presentation in pediatric patients requires vigilance and prompt diagnosis given the disastrous and irreversible complications.